The Role of IL-27 and its Receptor in the Pathogenesis of HIV/AIDS and Anti-viral Immune Response - Zheng, Yu-Huang; Xiao, Shui-Ling; He, Bo; He, Yan; Zhou, Hua-Ying; Chen, Zi; Zheng, Li-Wen; He, Mei; Wang, Hong-Yan; Lin, Yi-He; Cao, Jing (Current HIV research, 2017)
Cytokines have been widely demonstrated to involve in the pathogenesis of AIDS and the mechanisms of antiretroviral therapy. Interleukin 27 (IL-27) is a new member of the IL-12 cytokine family and has been shown to interfere HIV-1 virus replication with controversial findings. This study is to investigate the dynamic changes in plasma IL-27 level and cell surface IL-27 receptor expression in HIV/AIDS patients who underwent HAART. Whole blood was collected from 34 HIV-positive/AIDS patients 0, 6, and 12 months after initiation of HAART and 27 healthy subjects. Plasma IL-27, IFN-γ, and IL-4 were measured by enzyme-linked immunosorbent assay, while peripheral blood CD3+CD4+ T cells count and the gp130 expressed CD3+CD4+cell were measured by flow cytometry. The plasma IL-27 concentration, IFN-γ concentration, and percentage of positive gp130 CD4 cells were significantly decreased in previously treatment-naive HIV/AIDS patients compared to healthy controls, but gradually increased 6 and 12 months after initiation of HAART. Conversely, IL-4 levels were significantly increased in treatment-naive HIV/AIDS patients compared to healthy controls, but gradually decreased 6 and 12 months after HAART. The concentrations of plasma IL-27 were positively correlated with the percentage of gp130 positive CD4 cells (r=0.438, p=0.016). Both plasma IL-27 concentration and gp130 positive cell percentage were positively associated with peripheral blood CD3+CD4+ T cell count (P<0.05 or P<0.01), but negatively associated with plasma HIV viral load (P<0.05 or P<0.01). IL-27 signaling (IL-27 and its receptor) may be involved in the pathogenesis of HIV infection and immune reconstitution in HIV/AIDS patients who underwent HAART. IL-27 may exert effects through regulating Th1 / Th2 ratio.